2011
DOI: 10.1002/cta.673
|View full text |Cite
|
Sign up to set email alerts
|

A new hyperchaotic Lorenz‐type system: Generation, analysis, and implementation

Abstract: SUMMARYA new four-dimensional continuous-time autonomous hyperchaotic Lorenz-type system is introduced and analyzed. This hyperchaotic system is not only visualized by computer simulation but also verified with bifurcation analysis and realized with an electronic circuit. Moreover, explicit formulae for estimating the ultimate bound and positive invariant set of the system are derived by constructing a family of generalized Lyapunov functions. The findings and results of this paper have good potential in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
(62 reference statements)
1
31
0
Order By: Relevance
“…We used MATLAB20 11 a for the simu lation and step size was 0.005 s. We used ode4 solver to solve the ordinary differential equation. We assumed that the drive system as a complex Chen system [15], which is 3rd order, and response system as a hyperchaotic complex Lorentz type system [16], which is 4th order. The nonlinear equations of drive system and response system are defined as follows: Hyperchaotic complex Lorentz-type system: …”
Section: Numerical Examplementioning
confidence: 99%
“…We used MATLAB20 11 a for the simu lation and step size was 0.005 s. We used ode4 solver to solve the ordinary differential equation. We assumed that the drive system as a complex Chen system [15], which is 3rd order, and response system as a hyperchaotic complex Lorentz type system [16], which is 4th order. The nonlinear equations of drive system and response system are defined as follows: Hyperchaotic complex Lorentz-type system: …”
Section: Numerical Examplementioning
confidence: 99%
“…Recently, Li et al [45] proposed a new hyperchaotic Lorenz-type system described by and its attractor is shown in Figure 1. Lately, Dadras et al [46] reported the following four-wing hyperchaotic system, which has only one unstable equilibrium…”
Section: Description Of the Switched Generalized Function Projective mentioning
confidence: 99%
“…When a = 8, b = 40 and r = 14.9, and with the initial condition [10,1,10,1] T , system (5) is hyperchaotic and its attractor is shown in Figure 2. For more information on the dynamical behaviors of these two systems, please refer to [45,46].…”
Section: Description Of the Switched Generalized Function Projective mentioning
confidence: 99%
“…The ever present demand for secure communication is one of the foremost form of motivation for studying chaos synchronization [4][5][6]. Various linear and nonlinear control techniques have been developed to carry out synchronization behavior.…”
Section: Introductionmentioning
confidence: 99%